2020
DOI: 10.1186/s12957-020-01947-z
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on the oncogenic mutation and molecular pathology in Chinese lung adenocarcinoma patients

Abstract: Background: Several genetic driver alterations have been identified in micropapillary lung adenocarcinoma (MPA). However, the frequency of co-alteration of ROS1, EGFR, and EML4-ALK is yet unclear. Herein, we investigated the relationship between clinicopathologic characteristics and well-identified driver mutations of MPA compared with non-micropapillary lung adenocarcinoma (LA). Methods: Formalin-fixed paraffin-embedded (FFPE) sections derived from lung adenocarcinoma patients who never received adjuvant chem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…With the rapid advances in modern molecular biology technology, the treatment model for lung cancer has focused on targeting abnormal molecules in specific signaling pathways [ 5 , 6 ]. In the past 10 years, tyrosine kinase inhibitors (TKIs) for epidermal growth factor receptor (EGFR) have demonstrated remarkable clinical effects and paved the way for effective treatment of lung cancer [ 7 9 ]. Indeed, a recent phase III clinical trial (ADAURA [NCT02511106]) assessed the efficacy and safety of a 3rd-generation EGFR-TKI, osimertinib, which had superior efficacy when compared to EGFR-TKI (gefitinib/erlotinib) in treatment-naïve patients with EGFR-mutated advanced NSCLC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid advances in modern molecular biology technology, the treatment model for lung cancer has focused on targeting abnormal molecules in specific signaling pathways [ 5 , 6 ]. In the past 10 years, tyrosine kinase inhibitors (TKIs) for epidermal growth factor receptor (EGFR) have demonstrated remarkable clinical effects and paved the way for effective treatment of lung cancer [ 7 9 ]. Indeed, a recent phase III clinical trial (ADAURA [NCT02511106]) assessed the efficacy and safety of a 3rd-generation EGFR-TKI, osimertinib, which had superior efficacy when compared to EGFR-TKI (gefitinib/erlotinib) in treatment-naïve patients with EGFR-mutated advanced NSCLC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous study demonstrated that micropapillary lung adenocarcinoma had a signi cantly higher tumor mutation burden, such as EGFR mutations, ROS1 fusions. And the incidence of coexisting between EGFR mutations and ROS1 fusions was higher than that other lung adenocarcinoma subtypes [14]. Warth [15] et al also found that patients with micropapillary structure had a signi cantly higher prevalence of driver genetic alterations and rearrangements of ROS1 or ALK than that other histological lung adenocarcinoma subtypes.…”
Section: Introductionmentioning
confidence: 96%
“…EGFR mutations were identified in 40–60% of lung adenocarcinomas in East Asians, and exon19 and exon 21 accounted for 87% [ 5 , 6 ]. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have revolutionized the treatment of advanced NSCLC, leading to the investigation of adjuvant EGFR-TKI treatment for early-stage disease.…”
Section: Introductionmentioning
confidence: 99%